Effects of potassium levels on growth and productivity of potato varieties in inner terai of Nepal - Panthi, Urbashi; Bartaula, Sampurna; Adhikari, Anil; Timalsena, Kiran; Khanal, Sagar; Subedi, Susan (Journal of Agriculture and Natural Resources, 2019)
Potassium is an essential nutrient for potato due to its direct effects on the growth, yield and quality of potato tubers. This study was carried out at Lamahi, Dang Nepal during winter season of 2018. Two potato variety (Local and Cardinal) and five levels of potassium (30, 40, 60, 80 and 100 kg K2O/ha) were evaluated in two factorial randomized block design with three replications. The application of potassium at 100 kg/ha produced significantly highest plant canopy, stem diameter and leaf length for the both varieties. The highest tuber number per plant (10.3 for Local and 17.6 for cardinal) and tuber weight (19.7 g for Local and 49 g for Cardinal) were obtained with the application of 100 kg K2O/ha. The highest gross margin was found with this level of potassium. Therefore, farmers should apply 100 kg K2O to potato to achieve maximum production and benefit.